Valuation and pricing of software licenses to support supplier–buyer negotiations: A case study in the automotive industry - Frank Bodendorf; Manuel Lutz; Jörg Franke (Managerial and Decision Economics, 2021)
Licensed standard software can be replicated millions of times at near zero cost for the supplier and poses immense challenges for purchasing and cost managers. A model is introduced to evaluate the appropriateness of software prices and thus to support the negotiation and decision process regarding suppliers. The model determines the “value to customer” of a software product using conjoint analysis and converts that value into a theoretical license price. In a case study coming from a large Original Equipment Manufacturer (OEM) it is shown that the developed conjoint model can successfully be used in practice and suggests realistic purchase prices.
Keywords: 650